Molecular Interactions of Poly (methylmethacrylate), Poly (vinyl alcohol), Poly(ethylene glycol), Chitosan, Cellulose and Starch Polymers with Iodine - Jaleel Kareem Ahmed 1, Auda Jabbar Braihi2 , Duaa Abdul Rida3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The interactions betweenpoly(methylmethacrylate)(PMMA),poly(vinylalcohol) (PVA) poly(ethyleneglycol)(PEG)as industrial biopolymers andchitosan, cellulose, starch as natural biopolymers with iodine(I2)were investigated using diethyl ether as a solvent. 5% of I2 was added to each polymer and soaked in thesolvent. The interactions were investigated using concepts of the activation energy(Ea), Decisivefactor (Df)and the changing in the glass transition temperature (?Tg,s). Therefore, the differential scanning calorimeter(DSC) was used to monitorthe thermal transitions. The optical microscope(OM) device was used to studythe surface morphologies.Resultsshowed a clear depression in the glass transition temperatures (Tg,s) for allpolymers( as well as new colors appear) except cellulose still unaffected .It appears that cellulose moleculescoated with a film prevent iodine to diffuse through the network structure of cellulose thus no effected itscolor or its Tg which indicates that molecular structure of cellulose quite different from that of starch and forthis fact cellulose not soluble by a solvent and undigested in the human body. The depression inTg valuesof polymers indicate that iodine ruptures the engineering bonds of the polymers. The most effected Tg is ofchitosan (lowered by 40.23?C, this mean that iodine ruptures both hydrogen bonding through nitrogen andoxygen atoms in chitosan molecule.From Tg values, it seems that iodine can acts as moderate plasticizer, by diffusing through the net of syntheticand natural biopolymers ruptures their secondary bonds result in depression of their Tg except in case ofcellulose.The order of Tg depression is:Chitosan (40.23)>PMMA (27.89)>starch (22.29)>PVA (13.89) >PEG (5.78)>cellulose (0)Which showed no distinguish between natural and synthetic biopolymers.From Tg values calculation of the energy given by the addition of iodine to the polymers was done andshown the following order:chitosan(27.394)>PMMA(18.442) =starch(18.414)>PVA(9.316 )>PEG(4.315)>cellulose( 0 )